Psoriatic Arthritis Quality of Life Questionnaire: results of translation, cultural adaptation and validation in Russian language - I. F. Fairushina; D. I. Abdulganieva; S. P. McKenna; A. Сoffey (Современная ревматология, 2023)
Psoriatic arthritis (PsA) is a chronic progressive disease from the pondyloarthritis group of diseases. In recent years, there has been a significant increase in the incidence of PsA and cases of its severe course, with significant influence on the quality of life (QoL) of patients and early disability. Psoriatic Arthritis Quality of Life Questionnaire (PsAQoL) is the first quality of life questionnaire designed specifically for PsA that has not been previously validated in Russia.Objective: to translate the original PsAQoL questionnaire into Russian and evaluate the psychometric properties of the Russian version.Material and methods. The original PsAQoL was translated into Russian using two translational panels. In all, 12 local residents were included in the translation stage of the study. The external and logical validity of the questionnaire was assessed. Further, Russian-speaking patients with an established diagnosis of PsA (n=10) tested the questionnaire. A separate cohort of patients with PsA (n=50) was enrolled in a postal test retest study on 2 occasions, 2 weeks apart. Clinical data and the Medical Outcomes Study-Short Form (SF-36) questionnaire were used to assess convergent validity.Results and discussion. The Russian version of PsAQoL was relevant, clear, and easy to complete (6.1 minutes on average). PsAQoL had high internal consistency (Cronbach's á=0.87) and excellent retest validity (r>0.85). PsAQoL scores correlated most strongly with the SF-36 General Health Scale (r=-0.68, p<0.01). PsAQoL score did not depend on sex and age (p>0.05). The PsAQoL could distinguish between groups of patients defined by self-reported general health status and self-reported severity of PsA.Conclusion. The Russian version of PsAQoL proved to be understandable and easy to complete, as well as a reliable and valid tool for assessing the quality of life of patients with PsA.